FAKTOR – FAKTOR YANG MEMPENGARUHI PARTISIPASI IBU-IBU DALAM MENGIKUTI SENAM AEROBIK DI DESA RAWA MULYA KECAMATAN XIV KOTO KABUPATEN MUKOMUKO - Siti Aminah; Muhammad Sazeli Rifki (Jurnal IKEOR, 2023)
The development of sports in Indonesia is growing rapidly. This development is marked by the large number of people who carry out sports activities with great joy and of their own accord. Aerobics is an easy sport so that the enthusiasm of the community, especially mothers, is very high. Furthermore, they do it with different goals. The aim of this study was to determine the factors that influence the participation of mothers in participating in gymnastics in the village of Rawa Mulya XIV KOTO, Mukomuko Regency. This research was conducted at the Rawa Mulya Village Hall. The sample of this research is 60 people. The analysis used was univariate, bivariate and multivariate tests. The results of this study indicate that there is a relationship between age (p=0.001), health (p=0.003), social (p=0.002) and family support (p=0.000) to participation in aerobics in Rawa Mulya Village. The results of the multivariate test showed that the health factor variable was the most influential variable with the largest OR value of 8.855.